Hydrogen peroxide sensor: uniformly decorated silver nanoparticles on polypyrrole for wide detection range - Nia, P.M.; Meng, W.P.; Alias, Y. (2015)
Electrochemically synthesized polypyrrole (PPy) decorated with silver nanoparticles (AgNPs) was prepared and used as a nonenzymatic sensor for hydrogen peroxide (H2O2) detection. Polypyrrole was fabricated through electrodeposition, while silver nanoparticles were deposited on polypyrrole by the same technique. The field emission scanning electron microscopy (FESEM) images showed that the electrodeposited AgNPs were aligned along the PPy uniformly and the mean particle size of AgNPs is around 25 nm. The electrocatalytic activity of AgNPs-PPy-GCE toward H2O2 was studied using chronoamperometry and cyclic voltammetry. The first linear section was in the range of 0.1-5 mM with a limit of detection of 0.115 mu mol l(-1) and the second linear section was raised to 120 mM with a correlation factor of 0.256 mu moll(-1) (SIN of 3). Moreover, the sensor presented excellent stability, selectivity, repeatability and reproducibility. These excellent performances make AgNPs-PPy/GCE an ideal nonenzymatic H2O2 sensor. (C) 2015 Elsevier B.V. All rights reserved.